The Effectiveness Of English Interactive Media In Teaching Writing (An Experimental Study Conducted For Eleventh Graders In SMA N 1 Sedayu, Bantul Yogyakarta) - Gurbangeldiyewna, Atayewa Merjen; Hermayawati, Hermayawati ((JELE) Journal Of English Language and Education, 2017)
The objectives of the study are to find out the ability of the students in writing descriptive text both before and after the treatment either at control group or experiment group; to find out the effectiveness of Interactive Media for teaching writing descriptive text; to find out what writing elements that received significant improvement after being taught by Interactive Media. This research was conducted using experimental study to overcome students’ problem in learning English especially writing skill. The researcher used two classes as the subject: XI MIPA-1 as the experiment group and XI MIPA-4 as control group. Those MIPA classes belong to Argo Mulyo High School /SMA N 1 Sedayu, Argomulyo, Bantul.The experimental class was taught the descriptive text by using Interactive Media in the form of Macromedia Flash while control groupwas taught by using non-computer based lessons. Total sample of both classes were 60 students. The research was conducted within quasi-experiment study which used pre-post tests design of experiment and control groups. The researcher used this method in order to find out whether computer-based instruction/Interactive Media could make significant improvement on the students’ descriptive writing skill. Such effectiveness was seen from difference of means between pre-post of both control and experiment groups and its t-test score at the degree of significancy. The t-test was higher than the t-table, Interactive Media then was proved significancy in improving the students’ writing descriptive text skill. The students’ writing was analyzed and scored based on rubrics postulated by Brown and Bailey including paragraph organization, its content, language structure, vocabulary and mechanics. The experiment shows that the t-test was (3.16) which is higher than t-table (2.000). The aspects of wtiting that has significant improvement were content, organization, structure, vocabulary - means pre-test of experimental group = 76.5 and control group = 70.8 increased into, experimental group = 87.22 and control group = 78.8 during post test with standard deviation of experimental group = 7.7 and control group = 9.97. Since there was a significant improvement of students’ writing skill by using Interactive Media, this research then confirms that Interactive Media is effective for teaching writing at SMA level.